Centrifugal compressors : A strategy for aerodynamic design and analysis - Aungier, Ronald H. (ASME Press, 2000)
Introduction - Thermodynamics - Fluid mechanics - The impeller work input - One-dimensional aerodynamic performance analysis - Preliminary aerodynamic design and component sizing - General gas path and impeller design - Vaneless diffuser design - Vaned diffuser design - Return system design - Volute design - Quasi-three-dimensional flow analysis - Potential flow analysis in the blade-to-blade plane - Time-marching analysis of the blade-to-blade plane flow - Boundary layer analysis - Answers to exercises.